Treatment outcomes of Epstein-Barr virus associated nasopharyngeal carcinoma with three-dimensional conformal radiotherapy: A retrospective review - Viranna, Santhuri (Division of Radiology, 2023)
Background: Data on treatment outcomes of Epstein-Barr virus (EBV) associated nasopharyngeal carcinoma (NPC) largely comes from endemic regions. There is limited literature available regarding the epidemiology and treatment outcomes of EBV associated NPC in South Africa. Aim: The primary aim of the study was to determine overall survival (OS) of patients with EBV associated NPC treated over an 11-year period. Setting: Groote Schuur Hospital, between January 2003 and December 2013. Methods: This is a retrospective observational study. Medical records of all patients with histologically confirmed NPC were reviewed. EBV staining was requested on all available archived specimens. All radical patients were treated with three-dimensional conformal radiotherapy (3DCRT). This review assesses the prevalence of EBV associated NPC, OS, disease-free survival (DFS), loco-regional control (LRC), and impact of treatment interruptions on OS. Results: The study population comprised 53 patients. Non-keratinizing carcinoma was the primary histological subtype (86.8%). 25 patients (47.2%) had histologically confirmed EBV positive NPC. The 2-and 5-year OS of radically treated EBV positive patients were significantly higher than EBV negative patients, 84% versus 34% and 45% vs 17% respectively (p=0.002). Two-year DFS was 55% vs 43% (p=0.38) and 2-year LCR were 76.2% vs 46.2% (p=0.13) for EBV positive and EBV negative patients respectively. The mean OS of patients with treatment interruptions was lower compared to those without interruptions (1249 days vs 1440 days). Conclusion: Treatment of EBV associated NPC is associated with superior OS, with a nonsignificant trend for improved DFS and LRC, compared to EBV negative tumours.